The association between experiences of racism and mental health on children and young people in the UK: rapid scoping review - Fiyory Tzeggai Ghezae; Zonke Zungu; Ann John; Kadra Abdinasir; Kamaldeep Bhui; Adenike Adebiyi; Cathy Creswell (BJPsych Open)
Background Racism is increasingly recognised as a key contributor to poor mental health. However, the existing literature primarily focuses on its effects on adults.